2015
DOI: 10.1371/journal.pone.0130827
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Polymorphisms Associated with Hearing Threshold Shift in Subjects during First Encounter with Occupational Impulse Noise

Abstract: Noise-induced hearing loss (NIHL) is the most significant occupational health issue worldwide. We conducted a genome-wide association study to identify single-nucleotide polymorphisms (SNPs) associated with hearing threshold shift in young males undergoing their first encounter with occupational impulse noise. We report a significant association of SNP rs7598759 (p < 5 x 10-7; p = 0.01 after permutation and correction; Odds Ratio = 12.75) in the gene coding for nucleolin, a multifunctional phosphoprotein invol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
12
0
7

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 92 publications
0
12
0
7
Order By: Relevance
“…Today in 2017, over 3000 human GWAS have examined over 1800 diseases and traits, and thousands of SNP associations have been found. In our knowledge, GWAS in nonsyndromic hearing research was studied in the 1990´s, and after that dozens of studies have found over 100 SNPs associated with different hearing related traits, such as normal hearing [100], ARHL [101][102][103][104], NIHL [105,106] and cisplatin induced ototoxicity [107].…”
Section: Genome-wide Association Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Today in 2017, over 3000 human GWAS have examined over 1800 diseases and traits, and thousands of SNP associations have been found. In our knowledge, GWAS in nonsyndromic hearing research was studied in the 1990´s, and after that dozens of studies have found over 100 SNPs associated with different hearing related traits, such as normal hearing [100], ARHL [101][102][103][104], NIHL [105,106] and cisplatin induced ototoxicity [107].…”
Section: Genome-wide Association Studiesmentioning
confidence: 99%
“…A population-based Polish study by Kowalski et al, (2014) investigated a genetic variation playing a role in determining individual susceptibility to the development of NIHL, especially, in young adults and in those exposed to impulse noise and they concluded a cautious interpretation that a genetic variant may modify the susceptibility to NIHL development in humans [197]. A GWAS data by Grondin et al, (2015), showed a significant difference between the groups with and without hearing loss. Hearing thresholds were obtained before and after noise exposure, the hearing impaired group had worse hearing thresholds after noise exposure, in contrast, subjects performed similar in their hearing test before and after noise exposure [106].…”
Section: Comments (Paper Iii)mentioning
confidence: 99%
“…И только Y. Grondin и соавт. [21] использовали методику полногеномного ассоциативного поиска и обнаружили новые SNPs в гене нуклеолина (p<0,01), ассоциированные с тугоухостью, вызванной шумом. Популяционные исследования гена-кандидата преимущественно направлены на исследования SNPs в кодирующих участках гена, в то время как SNPs, возникающие в некодирующих областях генома, исследуются редко.…”
unclassified
“…Популяционные исследования гена-кандидата преимущественно направлены на исследования SNPs в кодирующих участках гена, в то время как SNPs, возникающие в некодирующих областях генома, исследуются редко. Полиморфизмы регуляторных областей могут дисрегулировать экспрессию белковых изоформ, а полиморфизмы некодирующих областей -воздействовать на экспрессию мРНК [21][22][23]. Тем не менее исследования на некоторых популяциях позволили определить гены, ассоциированные с риском развития профессиональной нейросенсорной тугоухости, условно разделяемые на четыре группы (см.…”
unclassified
See 1 more Smart Citation